A comparison of the effects of El Niño and El Niño Modoki on subdaily extreme precipitation occurrences across the contiguous United States. Issue 14 (26th July 2017) - Yu, Lejiang; Zhong, Shiyuan; Heilman, Warren E.; Bian, Xindi
Abstract: Intense precipitation over a short duration is a major cause of flash floods. Using hourly rainfall data from the North America Land Data Assimilation System Phase 2 from 1979 to 2013, we compared the differences in the response of the subdaily extreme precipitation occurrences across the contiguous U.S. to strong anomalous warming over the eastern equatorial Pacific known as El Niño and over the central equatorial Pacific known as El Niño Modoki. For both types of anomalous equatorial Pacific warming, the teleconnection is much stronger in the cold season (November through April) than warm season (May through October). During the warm season, while both types correspond to an increase in subdaily extreme precipitation in areas of Texas and a decrease in some areas of the northern Plains, El Niño is associated with a significant increase in the northern Rockies and El Niño Modoki is associated with a decrease in the Intermountain West. During the cold season, the overall patterns are similar between the two types, with positive anomalies over much of the southern and negative anomalies over the northern U.S. However, large regional differences exist, with El Niño exerting a much stronger influence on subdaily extreme precipitation in the Atlantic and Gulf states as well as California, while the influence of El Niño Modoki is slightly broader over the Midwest. These differences can be largely explained by the vertical velocity, moisture convergence, and jet stream patterns induced by El Niño and El Niño Modoki episodes. Key Points: Significant regional differences exist in the occurrences of subdaily extreme rainfall in the U.S. during El Niño and El Niño Modoki Cold‐season extreme rainfall occurrences in the U.S. respond more strongly to El Niño than to El Niño Modoki Their influences differ significantly in the Mountain States for the warm season and along the East/Gulf Coasts and CA for the cold season